On the debate around immanence and transcendence: Multitude or the people - Perelló, Gloria (2012)
There has been a profound debate about new ways of looking on emancipatory politics among progressive political theoreticians. One of the most important consequences of this contemporary debate has been the emergence of three related controversies: transcendence versus immanence, the people versus the multitude and negative ontology versus positive ontology. Our argumentative strategy will be to present these controversies first, through Hardt and Negri's point of view, and then through a Lacanian lecture of Laclau's perspective, author who places the psychoanalysis where philosophy traditionally located ontology.